2014
DOI: 10.1371/journal.pone.0102353
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Cancer Care for Young Patients with Nasopharyngeal Carcinoma in Jakarta, Indonesia

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is endemic in Indonesia and 20% of the patients are diagnosed before the age of 31. This study evaluates presentation and treatment outcome of young patients in Jakarta, in a tertiary referral centre.MethodsForty-nine patients under the age of 31, diagnosed with NPC between July 2004 and January 2007, were evaluated. Baseline data included histological type, stage of disease and presenting symptoms. We intended to follow all patients after diagnosis to reveal treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 28 publications
1
24
0
9
Order By: Relevance
“…The prevalence of nasopharynx cancer in developing countries is higher, and this is attributed to the higher exposure of inhabitants to a variety of risk factors and lower budget allocations for health. For these people, diagnosis is often made when the disease is already in advanced stages, and, with the lack of access to treatment, the metastasis of nasopharynx cancer can be observed more often in these areas 36, 37.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of nasopharynx cancer in developing countries is higher, and this is attributed to the higher exposure of inhabitants to a variety of risk factors and lower budget allocations for health. For these people, diagnosis is often made when the disease is already in advanced stages, and, with the lack of access to treatment, the metastasis of nasopharynx cancer can be observed more often in these areas 36, 37.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only about 14% of patients who have metastasis at the initial diagnosis and 29% of patients without metastasis show response to therapy, about 70–95% response to therapy is good, so in general response to the therapy is poor. [36]. In Singapore, older patients diagnosed with stage 2 or stage 3 are at higher risk of recurrence and lower overall survival [47].…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal cancer prevalence in countries with medium and low HDI is greater due to higher exposure to a variety of risk factors related to the cancer and less budget allocations for health. Therefore, because of the diagnosis at an advanced stage and lack of access to treatment, metastasis of nasopharynx cancer can be observed more in these areas [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…; treatment response, LRC, DFS and OS. This was based on experience from previous studies where we found difficulties completing follow up data [ 4 , 30 ]. For every analysis, some patients had to be excluded due to uncertainty.…”
Section: Discussionmentioning
confidence: 99%